Integrated Assessment of Nickel Electroplating Industrial Wastewater Effluent as a Renewable Resource of Irrigation Water Using a Hydroponic Cultivation System - Chow, Y. N.; Lee, L. K.; Zakaria, N. A.; Foo, K. Y. (Frontiers in Plant Science, 2021)
Nickel, a micronutrient essential for plant growth and development, has been recognised as the metallic pollutant in the wastewater. The concentration of nickel ions in the water course, exceeding the maximum tolerable limit, has called for an alarming attention, due to the bioaccumulative entry in the water-plant-human food chain, leaving a burden of deteriorative effects on visible characteristics, physiological processes and oxidative stress response in plants. In this work, the renewable utilization of nickel electroplating industrial wastewater effluent (0%, 5%, 10%, 25%, 50%, 100%) as a viable source of irrigation water was evaluated using a hydroponic cultivation system, by adopting Lablab purpureus and Brassica chinensis as the plant models, in relation to the physical growth, physiological and morphological characteristics, photosynthetic pigments, proline, and oxidative responses. The elongation of roots and shoots in Lablab purpureus and Brassica chinensis were significantly inhibited beyond 25% and 5% of industrial wastewater. The chlorophyll-a, chlorophyll-b, total chlorophyll, and carotenoid contents, accompanied by alterations in the morphologies of xylem, phloem and distortion of stomata, were recorded in the industrial wastewater-irrigated groups, with pronounced toxicity effects detected in Brassica chinensis. Excessive proline accumulation was recorded in the treated plant models. Ascorbate peroxidase (APX), guaiacol peroxidase (POD), and catalase (CAT) scavenging activities were drastically altered, with a profound upregulation effect in the POD activity in Lablab purpureus, and both POD and APX in Brassica chinensis, predicting the nickel-induced oxidative stress. Conclusively, the diluted industrial wastewater effluent up to the optimum concentrations of 5% and 25%, respectively, could be feasibly reused as a renewable resource for Brassica chinensis and Lablab purpureus irrigation, verified by the minimal or negligible phytotoxic implications in the plant models. The current findings have shed light on the interruption of nickel-contaminated industrial wastewater effluent irrigation practice on the physical and biochemical features of food crops, and highlighted the possibility of nutrient recycling via wastewater reuse in a sustainable soilless cultivation.